2014
DOI: 10.1016/j.tig.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The overdue promise of short tandem repeat variation for heritability

Abstract: Short tandem repeat (STR) variation has been proposed as a major explanatory factor in the heritability of complex traits in humans and model organisms. However, we still struggle to incorporate STR variation into genotype-phenotype maps. Here, we review the promise of STRs in contributing to complex trait heritability, and highlight the challenges that STRs pose due to their repetitive nature. We argue that STR variants are more likely than single nucleotide variants to have epistatic interactions, reiterate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 98 publications
1
102
0
5
Order By: Relevance
“…Interestingly, we found that loci with dinucleotide motifs show relatively weak LD with SNPs, suggesting that GWAS studies with SNP arrays are prone to miss causal STR loci. Given the theoretical potential of STRs to contribute to phenotypic variance on one hand and their weaker LD to tagging SNPs on the other hand, one intriguing possibility is that STRs contribute to the missing heritability phenomenon of complex traits (Manolio et al 2009;Press et al 2014). Our hope is that this catalog can be a reference point to test this hypothesis in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that loci with dinucleotide motifs show relatively weak LD with SNPs, suggesting that GWAS studies with SNP arrays are prone to miss causal STR loci. Given the theoretical potential of STRs to contribute to phenotypic variance on one hand and their weaker LD to tagging SNPs on the other hand, one intriguing possibility is that STRs contribute to the missing heritability phenomenon of complex traits (Manolio et al 2009;Press et al 2014). Our hope is that this catalog can be a reference point to test this hypothesis in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the two approaches will yield much reliable and important information regarding repeat variation in natural populations. Such TR genotyping from wholegenome sequencing data will have a profound impact on many fields, from conservation genetics to forensics, and on elucidating the role of TRs in complex trait heritability (Press et al 2014).…”
Section: Tandem Repeats Increase Expression Divergencementioning
confidence: 99%
“…The most hypermutable microsatellites tend to have a high A/T content 26 and have a large number of repeated subunits. Because long microsatellites have a 27 tendency to contract more often than they expand [12], microsatellites undergo a 28 lifecycle in which they are "born" and "die" in the genome over evolutionary time [8,13]. 29 Tandem repeats composed of subunits greater than nine base-pairs are called 30 minisatellites.…”
mentioning
confidence: 99%
“…Tandem repeats have been hypothesized to be partially responsible 55 for missing heritability [18,27], and may also be partially responsible for some of the 56 still-missing heritability. Due to their high mutability, tandem repeats can mutate away 57 from linkage with surrounding SNPs, and therefore SNP association studies are not 58 expected to pick up all of the heritability caused by hypermutable variants.…”
mentioning
confidence: 99%